Trunk kinematics during the tee-shot of male and female golfers - Cole, H.; Grimshaw, P. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
While females comprise 20% of the golfing population in some Western countries (e.g. Australian Bureau of Statistics, 2007), previous research has typically assessed populations that are exclusively comprised of male golfers (e.g. Cheetham et al., 2008). However, the overall prevalence of golf-related injuries is reported to be similar for males and females (McHardy et al., 2006) and thus, it is of interest to assess whether the kinematics of the female golf swing are similar to those demonstrated by male players. This is important, as this knowledge will ensure that any changes that are made by coaches to improve performance and/or reduce the risk of injury in these golfers are appropriate.